Blood cadmium and physical function limitations in older adults. (1st May 2021) - García-Esquinas, Esther; Téllez-Plaza, María; Pastor-Barriuso, Roberto; Ortolá, Rosario; Olmedo, Pablo; Gil, Fernando; López-García, Esther; Navas-Acien, Ana; Rodríguez-Artalejo, Fernando
Abstract: Background: Cadmium (Cd) is a toxic metal found in tobacco, air and food. Recent cross-sectional studies have suggested that Cd negatively impacts physical performance, but the prospective association is uncertain. Methods: We used data from 2548 older adults from the Seniors-ENRICA II cohort in Madrid, Spain. Whole blood Cd levels were measured at baseline using inductively coupled plasma-mass spectrometry. At baseline (2017) and follow-up (2019), overall physical function was evaluated using the physical component summary (PCS) of the SF 12-Item Health questionnaire, lower-extremity performance with the Short Physical Performance Battery (SPPB), muscle weakness with a hand dynamometer, and frailty with a Deficit Accumulation index. Mobility limitations and disability in instrumental activities of daily living (IADL) were ascertained with standardized questionnaires. Analyses were adjusted for relevant confounders, including tobacco smoke, number of cigarettes smoked per day and time since cessation in former smokers. Results: In cross-sectional analyses, odds ratios (95% confidence interval) per two-fold increase in blood Cd were 1.16 (1.03; 1.31) for low PCS scores, 1.08 (0.97; 1.20) for impaired lower-extremity performance, 1.10 (0.98; 1.23) for low grip strength, 1.11 (1.02; 1.20) for mobility limitations, 1.16 (1.02; 1.31) for frailty, and 1.26 (1.08; 1.47) for IADL disability. In longitudinal analyses, corresponding hazard ratios were 1.25 (1.03; 1.51) for low PCS scores, 1.14 (1.03; 1.27) for impaired lower-extremity performance, 1.02 (0.92; 1.13) for low grip strength, 1.03 (0.91; 1.16) for mobility limitations, and 1.16 (1.00; 1.35) for frailty. All the associations where consistent when current smokers were excluded from the analyses. Conclusions: Our results support the role of Cd as a risk factor for physical function impairments in older adults. Graphical abstract: Image 1 Highlights: Functional decline in older adults is a major challenge to health care systems. Most of the few previous reports on Cd and functional decline are cross-sectional. We prospectively studied this association in older adults with low cadmium exposure. B–Cd levels were related to higher risk of limitations in several functional domains. Further efforts should be made to protect the elderly against Cd exposure.